PENERAPAN METODE DRILL UNTUK MENINGKATKAN PEMAHAMAN MATEMATIKA SISWA KELAS VIII SMP NEGERI 5 TANJUNG MORAWA - Ningsih, Raden Endang Retno (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
Subjects were students of SMP Negeri 5 Tanjung Morawa Academic Year 2015/2016 the number of students as many as 34 people. This study consisted of two cycles. Cycle I spent 3 meetings and the second cycle spent 2 meetings. The instrument used was a test and non-test. Mechanical tests the ability of understanding the mathematical form of a written test on each cycle, while the non-test techniques using instruments of observation of student activity and observation of activities of teachers manage learning. The results showed an increase from the first cycle and the second cycle, ie the first cycle obtained 61.76% of the students have met the criteria of mastery learning with an average value of 83.33. While on the second cycle was obtained 85.29% of the students have met the criteria of mastery learning with an average value of 83.70 and concluded an increase of 23.53% from the results of the test cycle I to cycle II.Â Key Words: Understanding of Mathematics, Methods Dril